Sensors: Detection Beyond Debye's Length with an Electrolyte‐Gated Organic Field‐Effect Transistor (Adv. Mater. 5/2015). (February 2015) - Palazzo, Gerardo; De Tullio, Donato; Magliulo, Maria; Mallardi, Antonia; Intranuovo, Francesca; Mulla, Mohammad Yusuf; Favia, Pietro; Vikholm‐Lundin, Inger; Torsi, Luisa
<x xml:space="preserve">Abstract</x> On page 911, G. Palazzo and co‐workers show how electrolyte gated organic field‐effect transistor (EGOFET) biosensors, can successfully detect, in highly concentrated salt solutions, binding occurring at distances from the transistor electronic channel that are much larger than the Debye length. The sensing mechanism is mainly capacitive and is due to the formation of Donnan's equilibria within the protein layer. The cover image is a "pop‐art" description of the sequential binding of streptavidin, biotinylated antibody, and C‐reactive proteins on the EGOFET sensor. Image by Daniele Romeo adapted from Palazzo's drawing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>